PENGOLAHAN SAMPAH ORGANIK RUMAH TANGGA DALAM PEMBUATAN KOMPOS UNTUK MENGURANGI DAMPAK PENCEMARAN - Dermawan, Sani; Ananda Zuhdi, Nadhila; Khalidah Hasibuan, Risna; Rahma Anjani, Mesy; Prayoga, Tandang; Destia Putri, Aura; Najwa, Shifa; Ayuni Devia Wani, Nur; Maryati; Yulita, Amelia (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
This community service program was implemented in Pekan Kamis Village with the aim of reducing household waste by making compost from kitchen waste. The village faces challenges in household waste management, which is often simply thrown away without further processing. To overcome this problem, training, and mentoring were provided to the mothers in Pekan Kamis Village participants so that they are skilled in making sustainable compost fertilizers. The methods used in this activity were socialization and training. The socialization aimed to provide a basic understanding of the importance of processing waste into useful products, while the training focused on compost making techniques, starting from the collection of organic materials, fermentation, to harvesting the compost. The results of this program showed an increase in residents’ understanding and skills regarding composting, as well as a decrease in the volume of household waste. In addition, this activity increases residents’ awareness of environmentally friendly waste management and provides economic benefits through the use of compost for agricultural purposes. Thus, this activity supports household waste reduction efforts and contributes to the environmental and economic welfare of the village community.